PENDAMPINGAN PENGGUNAAN ALAT POINT OFF CARE TEST (POCT) PADA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS MAKIAN, KECAMATAN MAKIAN, KABUPATEN HALMAHERA SELATAN - Husen, Samad Hi; Lewa, Irma B Hi; Nikma, Nikma (LP2M STP Mataram, 2024)
Type 2 diabetes mellitus is a metabolic disorder impacted by lifestyle factors, and it is a growing concern in Makian District, South Halmahera, North Maluku, where cases rose from 238 in 2022 to 357 in 2023. Limited access to healthcare in areas like Kywor Village hampers effective health monitoring, especially regular blood glucose checks for diabetes patients. Many patients lack knowledge about independent blood glucose monitoring using POCT (Point-of-Care Testing) devices, relying solely on health center visits. Without proper diabetes management, including regular blood glucose monitoring, the risk of severe complications increases. This community service initiative aimed to educate Makian health center patients on the POCT device's phlebotomy technique through pre-tests, lectures, demonstrations, and follow-up evaluations. Results were promising: pre-tests showed only 23.33% of 30 participants understood the technique, but post-test results indicated a significant improvement, with 83.33% demonstrating correct usage